THE ISSUE OF SPIRITUAL-MORAL, VALUE-BASED RELATIONSHIPS TOWARDS THE FAMILY IN THE PEDAGOGICAL VIEWS OF EASTERN AND WESTERN SCIENTISTS - Khaydarov Okhinjon Murodjonovich (Ecominds Press, 2025)
In this article, the pedagogical views of Eastern and Western scholars reflect the issue of spiritual, moral, value relations with the family. The article also considers the family as a public institution and describes the role of the family in the upbringing of children, the formation of spirituality and pedagogical views on family upbringing.
Keywords: Family, society, family relations, valuable attitude towards family, spiritual and moral relations, parents and children, education, family values, public institution.